Effect of biomass pre-treatment on supercritical CO2 extraction of lipids from marine diatom Amphora sp. and its biomass evaluation as bioethanol feedstock. Issue 1 (January 2021) - Hogan, Paul; Otero, Paz; Murray, Patrick; Saha, Sushanta Kumar
Abstract: Marine diatoms are a potential source for lipids and carbohydrates, which can have several applications ranging from biofuels to nutraceuticals. Due to their siliceous cellular structure and the complex nature of different lipid classes, it is important to understand the effect of biomass pre-treatment on the extractability of marine diatom lipids. In the present study, we tested the effect of four biomass pre-treatments (acid, base, anionic detergent, and non-ionic detergent) conditions on the extractability of lipids from Amphora sp. biomass. Lipids were extracted under identical supercritical fluid extraction (SFE) conditions from each of the above mentioned pre-treated biomass of Amphora sp. grown with or without silica. The fatty acids profile of saponified lipids was analysed by LC-MS. Results obtained in this study suggest each pre-treatment has a specific effect on the fatty acids profile. Therefore, depending on the downstream application of lipids (biodiesel or nutritional), both types of biomass and their pre-treatment conditions need to be considered. From the fermentation study for biomass evaluation as bioethanol feedstock, it was found that the complex carbohydrates of Amphora sp. biomass were easily convertible by autoclaving to monomer sugars, which were suitable for bioethanol production by yeast fermentation. Abstract : Biomass pre-treatment; Diatom Amphora sp.; Supercritical fluid CO2 extraction; Fatty acids profile; Bioethanol feedstock; Yeast fermentation.